Surveillance by Proxy: Sport and Security in a Modern Age. (August 2016) - Hassan, David
This article considers the growing emphasis countries hosting major sporting events place on the implementation of security and counterterrorism measures and the impact this approach has on the civil liberties of their citizens. From the seminal, and ultimately tragic, events of the Munich Olympics in 1972 until the most recent terrorist attack witnessed at a major sporting event—that which marred the close of the Boston marathon of April 2013—this piece reflects on the full extent of the impact counterterrorism measures have had on the activities of wider society, including the creation of an abnormal host setting prior to and during the sporting event in question, not to mention its legacy long after it has ended and focus is drawn to a new location. It suggests that there is a real danger that international sporting events create a convenient setting within which the impositions of security measures, which are only marginally justifiable in the context of the event in question, continue to be unquestioningly implemented.